A Journey Through the Nation’s Body: Tobias Smollett’s «The Expedition of Humphry Clinker» (ACME, 2017)
In this essay, I will offer some brief considerations on how the bodily metaphor is particularly apt to a critical reading of Tobias Smollett’s The Expedition of Humphry Clinker on several and diverse levels. More specifically, I will focus (i) on the fluid generic status of the novel and on its position within the corpus of eighteenth-century British fiction; (ii) on the writing and reading of the nation’s body considered in its relationship with the structure of the novel; and (iii) on the city/country relationship as it emerges in the description of London, which, I suggest, can be read in parallel with George Cheyne’s considerations in The English Malady. In fact, as I will argue, for both his Scottishness and his practice of «medicine-by-post» (Wild 2006), Cheyne is a key figure to investigate several aspects of Humphry Clinker.